Doxycycline in serum and bronchial secretions. Issue 2 (April 1976) - Hartnett, B J; Marlin, G E
Abstract : The concentration of doxycycline hydrochloride was measured in serum and bronchial secretions in five patients with chronic bronchitis receiving doxycycline orally in normal therapeutic dosage for seven days (200 mg day 1, 100 mg days 2 to 7). After the loading dose of 200 mg, serum concentrations ranged between 5-40 and 3-45 mug/ml (mean 4-33 mug/ml) at 3 hours, declining to between 2-28 and 1-21 mug/ml (mean 1-71 mug/ml) at 23 hours. The mean serum levels for days 2 to 7 were 2-15, 1-79, and 1-38 at 3, 8, and 23 hours respectively. There was considerable individual variability and a wide range of concentrations of doxycycline in the sputum (0-07 to 2-10 mug/ml, mean 0-34 mug/ml). During the course of treatment there was a progressive increase in sputum levels and sputum/serum concentration ratios. There was no correlation between sputum concentration and degree of purulence. The clinical efficacy of doxycycline does not appear to be related to sputum concentration, although the progressive increase in sputum doxycycline levels may be relevant in preventing recurrence of acute infection when the drug is administered as long-term prophylactic therapy.